Intervention focus moderates the association between initial receptive language and language outcomes for toddlers with developmental delay. (2nd October 2019) - Barker, R. Michael; Romski, MaryAnn; Sevcik, Rose A.; Adamson, Lauren B.; Smith, Ashlyn L.; Bakeman, Roger
Abstract: This ex-post facto study reanalyzed data from Romski et al. to examine whether intervention focus moderated the relationship between pre-intervention standardized measures of receptive language and post-intervention standardized measures of receptive and expressive language age and observations of expressive target vocabulary size. In all, 62 toddlers with developmental delay were randomly assigned to augmented communication-input (AC-I), augmented communication-output (AC-O), or spoken communication (SC) interventions. AC-I provided augmented language input via spoken language and a speech-generating device (SGD); AC-O encouraged the production of augmented output via an SGD; and SC provided spoken input and encouraged spoken output without using an SGD. Intervention focus moderated the impact of initial receptive language on expressive language age and expressive target vocabulary size. Participants in AC-I, when compared to those in the other two interventions, had a significantly stronger relationship between initial receptive language and post-intervention expressive language age. For expressive target vocabulary size, participants in AC-O showed a strong relationship and those in AC-I a slightly weaker relationship between initial receptive language and expressive target vocabulary size; no significant relationship was found in the SC group. Results emphasize that different interventions may have distinct outcomes for children with higher or lower initial receptive language.